DEVELOPMENT OF CONTROLLED RELEASE ANTIULCER TABLETS USING EXTRUSION- SPHERONIZATION METHOD AND STUDY OF EFFECT OF HYDROPHILIC POLYMERS ON RELEASE RATE AND IN VITRO EVALUATION - S. P. PHADATARE; K. K. SINGH (International Journal of Pharma and Bio Sciences, 2012)
The purpose of the present investigation was to develop controlled release ranitidine hydrochloride swelling matrix tablets using extrusion spheronisation method and HPMC K100M as release retardant, for once a day administration. This study evaluated the effects of formulation and process variables on the properties of pellets and the tablets were compressed from essentially spherical, free flowing pellets. Main effects related to excipients, extruder screen size, spheronizer speed and residence time were studied. Optimum parameters were selected to get pellets of good flowability, % sphericity, desired particle size distribution and best possible yield. Experiments demonstrated that changes in content of granulating agent, spheronisation speed and residence time can result in marked differences in the shape and percentage yield of spheroids in different size ranges. All the tablet formulations showed prolonged and consistent in-vitro drug release up to 17 -20 hours, the rate of drug release was diffusion controlled and follows Higuchi model. Higher polymer concentration retarded the drug release for longer period of time.